PEGylated versus Non-PEGylated pH-Sensitive Liposomes: New Insights from a Comparative Antitumor Activity Study - Shirleide Santos Nunes; Juliana de Oliveira Silva; Renata Salgado Fernandes; Sued Eustaquio Mendes Miranda; Elaine Amaral Leite; Marcelo Alexandre de Farias; Rodrigo Villares Portugal; Geovanni Dantas Cassali; Danyelle M. Townsend; Mônica Cristina Oliveira; André Luís Branco de Barros (Pharmaceutics, 2022)
PEGylated liposomes are largely studied as long-circulating drug delivery systems. Nevertheless, the addition of PEG can result in reduced interactions between liposomes and cells, hindering liposomal internalization into target cells. The presence of PEG on the surface of pH-sensitive liposomes is not advantageous in terms of biodistribution and tumor uptake, raising the question of whether the indiscriminate use of PEG benefits the formulation. In this study, two doxorubicin-loaded pH-sensitive liposomal formulations, PEGylated (Lip2000-DOX) or non-PEGylated (Lip-DOX), were prepared and characterized. Overall, the PEGylated and non-PEGylated liposomes showed no differences in size or morphology in Cryo-TEM image analysis. Specifically, DLS analysis showed a mean diameter of 140 nm, PDI lower than 0.2, and zeta potential close to neutrality. Both formulations showed an EP higher than 90%. With respect to drug delivery, Lip-DOX had better cellular uptake than Lip2000-DOX, suggesting that the presence of PEG reduced the amount of intracellular DOX accumulation. The antitumor activities of free-DOX and both liposomal formulations were evaluated in 4T1 breast tumor-bearing BALB/c mice. The results showed that Lip-DOX was more effective in controlling tumor growth than other groups, inhibiting tumor growth by 60.4%. Histological lung analysis confirmed that none of the animals in the Lip-DOX group had metastatic foci. These results support that pH-sensitive liposomes have interesting antitumor properties and may produce important outcomes without PEG.